Follow-Up and Outcome after Coronary Bypass Surgery Preceded by Coronary Stent Implantation - Hamiko, Marwan; Konrad, Nicole; Lagemann, Doreen; Gestrich, Christopher; Masseli, Franz; Oezkur, Mehmet; Velten, Markus; Treede, Hendrik; Duerr, Georg Daniel (The Thoracic and Cardiovascular Surgeon, 2023)
Background Guidelines on myocardial revascularization define recommendations for percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) surgery. Only little information exists on long-term follow-up and quality of life (QoL) after CABG preceded by PCI. The aim of our study was to evaluate the impact of prior PCI on outcome and QoL in patients with stable coronary artery disease who underwent CABG.Methods In our retrospective study, CABG patients were divided in: CABG preceded by PCI: PCI-first (PCF), and CABG-only (CO) groups. The PCF group was further divided in guideline-conform (GCO) and guideline nonconform (GNC) subgroups, according to the SYNTAX score (2014 European Society of Cardiology [ESC]/European Association for Cardio-Thoracic Surgery [EACTS] guidelines). Thirty days mortality, major adverse cardiac events, and QoL using the European Quality-of-Life–5 Dimensions were evaluated.Results A total of 997 patients were analyzed, of which 784 underwent CABG without (CO), and 213 individuals with prior PCI (PCF). The latter group consisted of 67 patients being treated in accordance (GCO), and 24 in discordance (GNC) to the 2014 ESC/EACTS guidelines. Reinfarction (PCF: 3.8% vs. CO: 1.0%; p = 0.024), re-angiography (PCF: 17.6% vs. CO: 9.0%; p = 0.004), and re-PCI (PCF: 10.4% vs. CO: 3.0%; p < 0.001) were observed more frequently in PCF patients. Also, patients reported better health status in the CO compared to PCF group (CO: 72.48 ± 19.31 vs. PCF: 68.20 ± 17.86; p = 0.01). Patients from the guideline nonconform subgroup reported poorer health status compared to the guideline-conform group (GNC: 64.23 ± 14.56 vs. GCO: 73.42 ± 17.66; p = 0.041) and were more likely to require re-PCI (GNC: 18.8% vs. GCO: 2.4%; p = 0.03). Also, GNC patients were more likely to have left main stenosis (GCO: 19.7% vs. GNC: 37.5%; p < 0.001) and showed higher preinterventional SYNTAX score (GCO: 18.63 ± 9.81 vs. GNC: 26.67 ± 5.07; p < 0.001).Conclusion PCI preceding CABG is associated with poorer outcomes such as reinfarction, re-angiography, and re-PCI, but also worse health status and higher rehospitalization. Nevertheless, results were better when PCI was guideline-conformant. This data should impact the Heart Team decision.
Keywords: coronary artery bypass graft surgery; percutaneous coronary intervention; quality of life